YgiM may act as a trigger in the sepsis caused by Klebsiella pneumoniae through the membrane-associated ceRNA network - Han, Mingxiao; Chen, Zhihao; He, Ping; Li, Ziyuan; Chen, Qi; Tong, Zelei; Wang, Min; Du, Hong; Zhang, Haifang (Frontiers in Genetics, 2022)
Sepsis is one of the diseases that can cause serious mortality. In E. coli, an inner membrane protein YgiM encoded by gene ygiM can target the eukaryotic peroxisome. Peroxisome is a membrane-enclosed organelle associated with the ROS metabolism and was reported to play the key role in immune responses and inflammation during the development of sepsis. Klebsiella pneumoniae (K. pneumoniae) is one of the important pathogens causing sepsis. However, the function of gene vk055_4013 which is highly homologous to ygiM of E. coli has not been demonstrated in K. pneumoniae. In this study, we prepared ΔygiM of K. pneumoniae ATCC43816, and found that the deletion of ygiM did not affect bacterial growth and mouse mortality in the mouse infection model. Interestingly, ΔygiM not only resulted in reduced bacterial resistance to macrophages, but also attenuated pathological manifestations in mouse organs. Furthermore, based on the data of Gene Expression Omnibus, the expression profiles of micro RNAs (miRNAs) and messenger RNAs (mRNAs) in the serum of 44 sepsis patients caused by K. pneumoniae infection were analyzed, and 11 differently expressed miRNAs and 8 DEmRNAs associated with the membrane function were found. Finally, the membrane-associated competing endogenous RNAs (ceRNAs) network was constructed. In this ceRNAs network, DEmiRNAs (hsa-miR-7108-5p, hsa-miR-6780a-5p, hsa-miR-6756-5p, hsa-miR-4433b-3p, hsa-miR-3652, hsa-miR-342-3p, hsa-miR-32-5p) and their potential downstream target DEmRNAs (VNN1, CEACAM8, PGLYRP1) were verified in the cell model infected by wild type and ΔygiM of K. pneumoniae, respectively. Taken together, YgiM may trigger the sepsis caused by K. pneumoniae via membrane-associated ceRNAs. This study provided new insights into the role of YgiM in the process of K. pneumoniae induced sepsis.